Representasi Maskulinitas Hegemonik dalam Iklan - Suprapto, Deddy (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2018)
This research aims at observing how advertisement define hegemonic masculinity and identifying the models of hegemonic masculinity in Indonesia. This research takes and focuses on Gudang Garam’s 2006–2010-released advertisements for the data. This research applies the analytical method of Fairclough's three-dimension of critical discourse analysis. First, the analysis is conducted by describing the advertisements. Then, the interpretation of the contexts of both the primary and secondary data. Finally, the explanation of the socio-cultural dimension. The results of this research shows that there are transformations on the representation of hegemonic masculinity from macho  to metrosexual, which is influenced by capitalism and consumerism. The transformation is only on the physical appearance, not in its essence.